Pengaruh Ekstrak Biji Kapulaga Terhadap Profil Hematologi dan Histopatologi Usus Ikan Gurame yang Diinfeksi Bakteri - Faridatun Amalia Hasanah; Arief Prajitno; Mohamad Fadjar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Gouramy (Osphronemus gouramy) is a freshwater fish with a high demand up to 40 tons/day. Bacterial attack (Edwardsiella tarda) is often a problem for aquaculture that interferes with fish health. The purpose of this study is to analyze the concentration of 70% ethanol extract of cardamom seeds (Amomum compactum) which is effective in treating carp infected with E. tarda bacteria in relation to hematology and intestinal histopathology. The research was conducted in February – June 2022 at the Fish Disease Laboratory, Universitas Brawijaya. The method used is the experimental method of Completely Randomized Design (CRD) with five treatments and three replications. The treatment used was soaking fish infected with E. tarda bacteria in a solution of 70% ethanol extract of cardamom seeds with concentrations of 250 mg/L, 275 mg/L, 300 mg/L, 325 mg/L and 350 mg/L. Parameters observed included changes in hematology, intestinal histopathology, survival rate and water quality. The results showed a significant change in hematological observations after being given the extract at a concentration of 300 mg/L with an average value of erythrocytes (3.16 x 106 cells/mm3), leukocytes (20.55 x 104 cells/mm3), lymphocytes (63%), neutrophils (14%) and monocytes (14%). The results of observations on changes in intestinal histology also showed damage in the form of necrosis, hemorrhage and edema before treatment and experienced the best decrease after administration of extract at a dose of 300 mg/L, namely 1.87 (necrosis), 1.33 (haemorrhage) and 1.27 (edema). The survival of carp infected with E. tarda bacteria after being given the extract for 24 hours and reared for 14 days experienced mortality of 67% (250 mg/L), 71% (275 mg/L), 78% (300 mg/L), 62% (325 mg/L) and 56% (350 mg/L). Meanwhile, observations of water quality showed results that were in accordance with the optimum value, so that it did not have a bad effect on the test fish. Based on the description of the results of this study, it can be concluded that the use of extracts at a concentration of 300 mg/L is the most effective dose to treat gourami infected with E. tarda bacteria.